Sérové protilátky proti annexinu V a jiným fosfolipidům m u zen s poruchou plodnosti - Ulcová-Gallová, Z; Turek, J; Bibková, K; Micanová, Z; Panzner, P; Balvín, M; Rokyta, Z (Ceska gynekologie, 2006)
THE AIM: To study serum antibodies against annexin V and against other phospholipids in women with fertility failure. DESIGN: Prospective study. SETTING: Department of Gynecology and Obstetrics, Institute of Imunology and Alergology, Institute of Forensic Medicine, Charles University and Faculty Hospital, Pilsen, Czech Republic. PATIENTS AND METHODS: We investigated sera from a total of 1550 women aged 26-41 years who attended the Division for Infertility and Reproductive imunology, in the Department of Obstetrics and Gynecology, Charles University, and Faculty Hospital, Pilsen, Czech Republic. ELISA was used for detection of antibodies against annexin V, phosphatidic (ph)-acid, ph-ethanolamine, D-L glycerol, ph-inositol, L-serine, cardiolipine, beta-glycoprotein, and prothrombine), antibodies against zona pellucida by passive hemmagglutination. Antibodies against annexin V in ovulatory cervical mucus were studied only in 47, and in follicular fluid in 168 women. Eighty-four fertile healthy women were included in the control group. RESULTS: Antibodies against annexin V were found in 13% (in 170 infertile women). Anamnestic data showed two or more unexplained pregnancy losses in 48 (28.2%), 108 (63.5%) patients had two or more unsuccessfull in vitro fertilization, polycystic ovaries (PCO) was diagnosed in 3 (1.7%), and endometriosis in 11 (6.6%) of them. The increased levels of antibodies against ph-inositole (28.8%), and L-serine (19.4%) were detected. 353% of patients had positive levels against zona pellucida. In ovulatory cervical mucus only in six (6/47) antibodies against annexin V were detected, in 5.55% in follicular fluid (6/108). CONCLUSION: Our study also demonstrated serum positivity against annexin V as a significant risk factor mainly in patiens with repeated reproductive failure.
Keywords: Humans; Female; lidé; autoprotilátky; ženské pohlaví; ženská infertilita; těhotenství; Abortion, Habitual; annexin A5; Infertility, Female; habituální potrat; Annexin A5; Antibodies, Antiphospholipid; Autoantibodies; dospělí; Pregnancy; Adult; antifosfolipidové protilátky; Cervix Mucus; cervikální hlen